Histomorphometry of umbilical cord and perinatal outcome in intrauterine growth restriction - S Kotrannavar, Sangeeta; A Dhumale, Hema; S Shirol, Veereshkumar; S Humbarwadi, Rajendra; B Javali, Shivalingappa; P Desai, Suresh (International Journal of Medical Research and Review, 2015)
Objective: To evaluate the histomorphometry of umbilical cord (UC) in intrauterine growth restricted (IUGR) newborns compared to appropriate for gestational age (AGA) newborns, and secondly to assess its impact on the intrapartum and perinatal outcome. Materials and Methods: A prospective observational study was conducted at Obstetrics and Gynecology unit of KLES Dr. Prabhakar Kore Hospital and Medical Research Centre, Belagavi. Study involved total 130 UCs of AGA and IUGR newborns. Tissues were fixed in formalin and paraffin embedded sections were examined. For each UC; UC cross sectional area (CSA), UC diameter and UC circumference parameters were measured under microscope with the help of digital image analyzer. Perinatal outcome like gestational age (GA) at delivery, birth weight, mode of delivery, sex of newborn, neonatal outcome and intrapartum complications were recorded. Independent t test was used to compare means and chi-square test for categorical variables. Results: UC of IUGR newborns had significantly reduced UC area, diameter and circumference as compared to AGA newborns. IUGR newborns were associated with significant difference in GA at delivery, birth weight, neonatal intensive care unit admissions (NICU) and fetal distress. No significant difference was found in mode of delivery, sex of newborn and meconium stained liquor among AGA and IUGR groups. Conclusion: Assessment of CSAs of UC and its components can be used as early screening tool for fetal growth and it may provide useful information about pregnancy at risk and help in averting poor perinatal outcome.